Iklim Kerja di PT Pelindo Terminal Petikemas TPK Bitung: Implikasi Terhadap Kesehatan dan Keselamatan Kerja - Chasy Ester Mandalika; Oksfriani Jufri Sumampouw; Afnal Asrifuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Work climate, particularly high ambient temperatures, significantly affects workers’ health and productivity. Extreme heat exposure may increase the risk of health issues, including cardiovascular diseases. This study aimed to assess the work climate conditions at PT Pelindo Terminal Petikemas TPK Bitung and evaluate the potential health risks for workers. This was a descriptive study using a quantitative approach. The variable measured was work climate, assessed using a Heat Stress Monitor during daytime shifts (08:20–19:40 WITA) with measurements taken every 40 minutes. Univariate analysis was used to describe the distribution of temperature parameters. The average work climate temperature was 29°C, with a minimum of 26°C and a maximum of 35.5°C. Based on the Indonesian Ministry of Manpower Regulation No. 5 of 2018, a Wet Bulb Globe Temperature (WBGT) of 29°C is within the safe threshold for light to moderate workloads but may exceed the Threshold Limit Value (TLV) under heavy physical exertion, especially under direct sunlight. The work climate at PT Pelindo Terminal Petikemas TPK Bitung presents varying levels of occupational health risk depending on the intensity and type of work performed. Preventive interventions are necessary to reduce the risk of heat stress.